Lymphopenia combined with low TCR diversity (divpenia) predicts poor overall survival in metastatic breast cancer patients - Manuel, Manuarii (Landes Bioscience, 2012)
Lymphopenia (< 1Giga/L) detected before initiation of chemotherapy is a predictive factor for death in metastatic solid tumors. Combinatorial T cell repertoire (TCR) diversity was investigated and tested either alone or in combination with lymphopenia as a prognostic factor at diagnosis for overall survival (OS) in metastatic breast cancer (MBC) patients. The combinatorial TCR diversity was measured by semi quantitative multi-N-plex PCR on blood samples before the initiation of the first line chemotherapy in a development (n = 66) and validation (n = 67) MBC patient cohorts. A prognostic score, combining lymphocyte count and TCR diversity was evaluated. Univariate and multivariate analyses of prognostic factors for OS were performed in both cohorts. Lymphopenia and severe restriction of TCR diversity called “divpenia” (diversity ≤ 33%) were independently associated with shorter OS. Lympho-divpenia combining lymphopenia and severe divpenia accurately identified patients with poor OS in both cohorts (7.6 and 10.6 vs 24.5 and 22.9 mo). In multivariate analysis including other prognostic clinical factors, lympho-divpenia was found to be an independent prognostic factor in the pooled cohort (p = 0.005) along with lack of HER2 and hormonal receptors expression (p = 0.011) and anemia (p = 0.009). Lympho-divpenia is a novel prognostic factor that will be used to improve quality of MBC patients’ medical care.